Investing with a Conscience: Exploring Individual Investors’ Intentions toward Socially Responsible Investment in Kathmandu Valley - Shrestha, Prabish; Lawaju, Purnima; Poudel, Devi Kumari (Quest Journal of Management and Social Sciences, 2025)
Background: The stock market plays a vital role in economic development by facilitating capital flow, reflecting investor sentiment, and enabling individual participation through liquidity and ownership, while behavioural finance highlights that investor decisions are often influenced by psychological biases rather than pure rationality. Purpose: The purpose of the study is to determine the behavioural intention of individual investors towards socially responsible investment in Kathmandu Valley. The study also examines the general understanding of individual investors regarding SRI, identifies major factors affecting the behavioural intention of individual investors towards SRI, assesses challenges faced by individual investors towards SRI and identifies possible managerial solutions to the challenges. Methods: An Explanatory research design is employed in this study. This study is based on the Theory of Reasoned Action. 403 investors investing in the equity market are taken as a sample by using the convenience sampling method and through self-administered questionnaires with the help of Kobo Toolbox. Data is examined through both descriptive and inferential statistics. SEM is used to analyse data. The study area is Kathmandu Valley. Findings: The study shows that investors are aware of SRI. Attitude, moral norms, financial performance, and environmental concerns directly affect investors' intention to invest in SRIs. Limited information on the companies being invested in and a lack of investment options are the significant challenges in SRI. The challenges can be minimised if companies are made to publish their CSR reports alongside their financial reports, which will make it simple to identify socially responsible businesses. Conclusions: This study concludes that individual investors' intention towards SRI is directly affected by attitude, moral norms, financial performance and environmental concern. Keywords: SRI Intention, Theory of Reasoned Action, Kathmandu valley, Structural Equation Modelling JEL Classification: C12, C83, G11, M14, O16